Uptake of intermittent preventive treatment for malaria during pregnancy with Sulphadoxine-Pyrimethamine (IPTp-SP) among postpartum women in Zomba District, Malawi: a cross-sectional study - Steven Chifundo Azizi; Gershom Chongwe; Helen Chipukuma; Choolwe Jacobs; Jessy Zgambo; Charles Michelo (BMC, 2018)
Abstract Background Malaria in pregnancy causes adverse birth outcomes. Intermittent preventive treatment of malaria during pregnancy with sulphadoxine-pyrimethamine (IPTp-SP) is recommended as a chemoprevention therapy. Zomba district IPTp uptake falls far below the national average. The study was conducted to assess determinants of IPTp-SP uptake during pregnancy among postpartum women in Zomba district after adoption of new IPTp-SP policy in 2014. Methods This was a cross-sectional survey. Two public health facilities (HFs) were randomly selected from urban and rural areas in Zomba district. Study participants were postpartum women selected by using exit poll method from HFs. A total of 463 postpartum women were interviewed using structured questionnaire. Bivariate and multiple logistic regression was used in data analysis. Results Out of all the enrolled participants (n = 463), 92% women had complete information for analysis. Of these, (n = 426) women, 127 (29.8%, 95% CI: 25.6%-34.3%) received three or more doses of SP, 299 (70.2%, 95% CI: 65.7%-74.4%) received two or less doses. Women receiving SP from rural HF were less likely to get at least three doses of SP than urban women, (AOR = 0.31, 95% CI 0.13-0.70); Others less likely were those with three or few antenatal care (ANC) visits versus four or more visits (AOR = 0.29, 95% CI 0.18-0.48); not taking SP under direct observation therapy (DOT) (AOR = 0.18, 95% CI (0.05-0.63). Conclusions There is low utilisation of at least three doses of SP in this population and this seems to be associated with the number of ANC visits and use of DOTs. These determinants may therefore be important in shaping interventions aimed at increasing the uptake of IPTp in this district. In addition, the rural urban differential suggests the need for further research to understand the barriers and enablers of uptake in each context in order to improve the health of the community.